External Debt Statistics : Guide for Compilers and Users. (Manuals and Guides, 2014)
The External Debt Statistics: Guide for Compilers and Users (EDS Guide) contains updated global standards for the compilation, reporting, and analytical use of external debt statistics. The 2013 EDS Guide was prepared under the responsibility of the nine organizations in the Inter-Agency Task Force on Finance Statistics, in close consultation with national compilers of external debt, balance of payments, and international investment position statistics, and reflects the significant developments in international finance since the issuance of the 2003 EDS Guide. The new edition provides guidance on the concepts, definitions, and classifications of external debt data; the sources and techniques for compiling these data; and the analytical uses of these data.